2018
DOI: 10.1016/j.bja.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine inhibits cytoskeletal remodelling and human breast cancer cell migration

Abstract: At clinical concentrations, lidocaine significantly inhibits CXCR4 signalling. The results presented shed new insights on the molecular mechanisms governing the inhibitory effect of lidocaine on cell migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 29 publications
4
40
0
Order By: Relevance
“…Beyond that, lidocaine also has many other pharmacological effects, like antipyroptosis [5], neuroprotection [6], cerebral protection [7], anti-inflammation [8], preventing mitochondrial dysfunction [9], and so forth. Moreover, recently paper reported the antitumour properties of lidocaine against diverse cancers, including colon adenocarcinoma [10], gastric cancer [11], breast cancer [12], and lung cancer [13]. Lidocaine significantly inhibited lung cancer cells proliferation [14] and made cancer cells more sensitive to cisplatin [13].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond that, lidocaine also has many other pharmacological effects, like antipyroptosis [5], neuroprotection [6], cerebral protection [7], anti-inflammation [8], preventing mitochondrial dysfunction [9], and so forth. Moreover, recently paper reported the antitumour properties of lidocaine against diverse cancers, including colon adenocarcinoma [10], gastric cancer [11], breast cancer [12], and lung cancer [13]. Lidocaine significantly inhibited lung cancer cells proliferation [14] and made cancer cells more sensitive to cisplatin [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the anticancer efficacies can be confirmed in various cancers, its exact mechanisms/targets remain unclear. As summarized in Table 1 and Figure 2 , the reported targets/mechanisms include MMP-9 ( Piegeler et al, 2015 ), ERK ( Chen et al, 2019 ), TRPV6 ( Jiang et al, 2016 ), and VEGF/VEGFR2 ( Gao et al, 2019 ), as well as the regulation of epigenetics ( Li et al, 2014 ), mi-RNA ( Qu et al, 2018 ; Sui et al, 2019 ; Yang Q. et al, 2019 ), inhibition of metastasis ( D’Agostino et al, 2018 ; Johnson et al, 2018 ; Sun and Sun, 2019 ), inhibition of inflammation ( Freeman et al, 2019 ), impacting mitochondrial metabolism ( Okamoto et al, 2017 ; Gong et al, 2018 ), the regulation of reactive oxygen species (ROS) ( Okamoto et al, 2016 ), etc. Importantly, as an ion channel regulator, lidocaine may exert its anticancer effects via regulation of other channels or membrane potential, such as mitochondrial membrane potential (MMP), which may lead to the decrease of MMP, finally resulting in the mitochondria-related apoptosis ( Li et al, 2014 ; Lu et al, 2016 ; Ye L. et al, 2019 ), providing valuable information for its targets identification.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…D’Agostino et al found that, lidocaine, at 10 and 100 μM, reduced the motility of human breast cancer MDA-MB-231 cells as measured by the scratch wound assay and chemotaxis experiments. Further study indicated that the effects were mediated by the suppression of CXCL12/CXCR4 signaling, leading to the down-regulation of calcium (Ca 2+ ) release and collapsed cytoskeleton remodeling, providing mechanistic insights of lidocaine in inhibiting cancer cell migration ( D’Agostino et al, 2018 ).…”
Section: Lidocaine In Cancer Treatmentmentioning
confidence: 99%
“…In combination with a microtubule inhibitor eribulin, POL5551 reduces metastasis and prolongs survival in vivo [ 126 ]. In another study, lidocaine blocked the CXCR4 signaling and decreased intracellular calcium release, cytoskeleton remodeling and cell migration in MDA-MB-231 cells [ 127 ]. The CXCR4-targeted dendrimers encapsulating doxorubicin also reduce CXCL12-induced migration of BT-549 and T47D breast cancer cells [ 128 ].…”
Section: Cxcl12/cxcr4-targeted Therapies Against Breast Cancermentioning
confidence: 99%